1986
DOI: 10.1002/pola.1986.080240205
|View full text |Cite
|
Sign up to set email alerts
|

Polynuclear and halogenated structures in polyphenylenes synthesized from benzene, biphenyl, and p‐terphenyl under various conditions: Characterization by laser desorption/fourier transform mass spectrometry

Abstract: SynopsisPolyphenylenes made by reaction of benzene, biphenyl, or p-terphenyl with metal halide catalyst-oxidant systems are complex mixtures of dissimilar oligomers, which include halogenated and polynuclear structures, according to positive and negativeion laser desorptionl Fourier transform mass-spectral analyses. Polymerization of benzene with metalchloride salts that terminate chain elongation by chlorination of the end rings appears to decrease formation of polynuclear structures by providing a competing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…Note that at this stage no water had been added to the system -the first step was only the production of a benzene/FeCl 3 dispersion to be mixed to water. Other oligomers may also be formed, such as biphenyl and para/ortho-terphenyl [28]. The presence of PPP is confirmed by the bands at 1221, 1265, 1338 and 1600 cm -1 , which are attributed to the C-H/C-C vibrations in the quinoid and benzenoid modes [29].…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Note that at this stage no water had been added to the system -the first step was only the production of a benzene/FeCl 3 dispersion to be mixed to water. Other oligomers may also be formed, such as biphenyl and para/ortho-terphenyl [28]. The presence of PPP is confirmed by the bands at 1221, 1265, 1338 and 1600 cm -1 , which are attributed to the C-H/C-C vibrations in the quinoid and benzenoid modes [29].…”
mentioning
confidence: 76%
“…Early in the 1960s, Kovacic et al reported several studies on the polymerization of aromatics with Lewis acids, in which polynuclear polyphenylenes were detected as side products under some experimental conditions [19,27,30]. These polynuclear macromolecules consist of condensed aromatic rings, resembling nanographene molecules [28,32,34]. While the exact structures are unknown, two pieces of the experimental evidences from the work of Kovacic et al support our hypothesis: first, PPP chains do not undergo crosslinking between them to produce polynuclear structures, but instead react with more benzene/FeCl 3 to produce an insoluble material with a high carbon content [32].…”
mentioning
confidence: 98%
“…It used AlCl 3 as a Lewis acid catalyst and CuCl 2 as an oxdidant. The polymer produced was a black material, containing a mixture of 1,2 (ortho) and 1,4 (para) units as well as chemical defects such as chlorination and intermolecular cross-links (Brown et al 1986;Berresheim et al 1999). The products should be more correctly defined as oligomers rather than polymers, as the chain lengths were between ten and 15 phenylene rings.…”
Section: Synthetic Approaches To Pppmentioning
confidence: 99%
“…Such a modification can involve the introduction of side chains, e.g., on benzene rings, or modification of the main chains, e.g., appropriate copolymerization. Also polynuclear moieties have been found in the above mentioned sexiphenyl fraction to a greater extent than by polymerization with benzene as well as chlorinated analogues that are similar to the products obtained from benzene (chlorination of the oligomer rings) [6,7,9]. the Kovacic procedure using benzene-aluminum chloride-cupric chloride) or other methods (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of biphenyl or terphenyl with catalyst-oxidant systems for dehydrocoupling has been the object of much less attention in comparison with the synthesis of PPP from benzene [9]. Besides, the doping treatment of polyphenylenes obtained from biphenyl has not been extensively studied.…”
Section: Introductionmentioning
confidence: 99%